2016
DOI: 10.4329/wjr.v8.i4.331
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography dose optimisation in cystic fibrosis: A review

Abstract: Cystic fibrosis (CF) is the most common autosomal recessive disease of the Caucasian population worldwide, with respiratory disease remaining the most relevant source of morbidity and mortality. Computed tomography (CT) is frequently used for monitoring disease complications and progression. Over the last fifteen years there has been a six-fold increase in the use of CT, which has lead to a growing concern in relation to cumulative radiation exposure. The challenge to the medical profession is to identify dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 118 publications
0
10
0
1
Order By: Relevance
“…A RM se mostra superior na avaliação de mudanças funcionais, como alterações na perfusão pulmonar. No entanto, é um exame menos sensível na detecção de doenças em pequenas vias aéreas (FERRIS et al, 2016). O RX de tórax é indicado em adolescentes e adultos, sendo solicitado as incidências póstero-anterior (PA) e uma em perfil.…”
Section: Discussionunclassified
“…A RM se mostra superior na avaliação de mudanças funcionais, como alterações na perfusão pulmonar. No entanto, é um exame menos sensível na detecção de doenças em pequenas vias aéreas (FERRIS et al, 2016). O RX de tórax é indicado em adolescentes e adultos, sendo solicitado as incidências póstero-anterior (PA) e uma em perfil.…”
Section: Discussionunclassified
“…Images are reconstructed with a sharp kernel lung algorithm to improve airway/air interface viewing. [34][35][36] The airways, lung parenchyma, and lung density have been extensively studied by using quantitative CT imaging in patients with asthma and other lung diseases. Airway characteristics, such as wall thickness, lumen area, and airway branching angle have been associated with asthma phenotypes and lung function outcomes, with segmental airway size negatively correlating with lung function (Fig 1).…”
Section: Chest Ctmentioning
confidence: 99%
“…Although catheter‐based angiography was historically the gold standard, CTPA is now the first‐line diagnostic option for PE in the general population, with excellent sensitivity and specificity for proximal and segmental PE 6–8 . Although PE is a potentially life‐threatening condition that merits thorough evaluation, the risks of kidney injury in CF patients receiving nephrotoxic antibiotics, as well as the cumulative risk of radiation exposure, particularly in young females, point toward the need to limit unnecessary use of CTPA 9 . A large single‐center study identified a total of four PE among 458 children with CF hospitalized over a 13‐year period 3 .…”
Section: Introductionmentioning
confidence: 99%